Mir-331-3p Inhibits PRRSV-2 Replication and Lung Injury by Targeting PRRSV-2 ORF1b and Porcine TNF-α - You, Xiangbin; Qu, Yilin; Zhang, Yue; Huang, Jingshu; Gao, Xiaoxiao; Huang, Chengyu; Luo, Gan; Liu, Qian; Liu, Min; Xu, Dequan (Frontiers in Immunology, 2020)
Porcine reproductive and respiratory syndrome (PRRS) caused by a single-stranded RNA virus (PRRSV) is a highly infectious respiratory disease and leads to huge economic losses to the swine industry worldwide. To investigate the role of miRNAs in the infection and lung injury induced by PRRSV, the differentially expressed miRNAs (DE-miRs) were isolated from PRRSV-2 infected/mock-infected PAMs of Meishan, Landrace, Pietrain, and Qingping pigs at 9, 36, and 60 hpi. Mir-331-3p was the only common DE-miR in each set of miRNA expression profile at 36 hpi. Mir-210 was one of 7 common DE-miRs between PRRSV infected and mock-infected PAMs of Meishan, Pietrain, and Qingping pigs at 60 hpi. Mir-331-3p/mir-210 could target PRRSV-2 ORF1b, bind and downregulate porcine TNF-α/STAT1 expression, and inhibit PRRSV-2 replication, respectively. Furthermore, STAT1 and TNF-α could mediate the transcriptional activation of MCP-1, VCAM-1, and ICAM-1. STAT1 could also upregulate the expression of TNF-α by binding to its promoter region. In vivo, pEGFP-N1-mir-331-3p could significantly reduce viral replication and pathological changes in PRRSV-2 infected piglets. Taken together, Mir-331-3p/mir-210 have significant roles in the infection and lung injury caused by PRRSV-2, and they may be promising therapeutic targets for PRRS and lung injury/inflammation.